Ultra-wear-resistant titanium alloy femoral condyle prosthesis and preparation method thereof, and artificial knee joint

By depositing a hard carbon-based film on the surface of the femoral condylar prosthesis of titanium alloy, the problem of high wear rate of polyethylene and allergic to nickel elements in artificial knee prosthesis is solved, and the titanium alloy femoral is realized The wear resistance of condylar prosthesis is improved and biocompatibility is improved.

CN117462745BInactive Publication Date: 2024-12-17浙江扶康生物科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311435030.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-01
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing cobalt-chromium-molybdenum alloy has a high wear rate on polyethylene in artificial knee prosthesis, and nickel allergy causes adverse reactions in some patients, seeking alternative materials to improve wear resistance and reduce adverse reactions.

Method used

Deposited hard carbon-based films on the surface of the titanium alloy femoral condyle prosthesis, including the bottom layer of titanium carbide, the transition layer of titanium carbide, the multi-layer of carbon-titanium carbide and the amorphous carbon top layer, are formed through magnetron sputtering technology to improve and enrich Friction properties of ethylene materials.

Benefits of technology

It significantly reduces the wear of polymer polyethylene gaskets, improves the wear resistance and biocompatibility of titanium alloy femoral condylar prosthesis, and reduces adverse reactions after prosthesis implantation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117462745B_ABST
    Figure CN117462745B_ABST
Patent Text Reader

Abstract

The present invention provides an ultra-wear-resistant titanium alloy femoral condyle prosthesis and a preparation method thereof, and an artificial knee joint. The ultra-wear-resistant titanium alloy femoral condyle prosthesis provided by the present invention comprises a titanium alloy femoral condyle matrix and a hard carbon-based film attached to the surface of the titanium alloy femoral condyle matrix; the hard carbon-based film comprises a titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer stacked in sequence; the titanium carbide bottom layer contacts the titanium alloy femoral condyle matrix; the carbon-titanium carbide multilayer consists of alternately stacked carbon layers and titanium carbide layers. The friction coefficient of the interface between the femoral condyle prosthesis provided by the present invention and the tibial pad (highly cross-linked polyethylene) is small, and has good friction reduction and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical devices, and in particular to a super-wear-resistant titanium alloy femoral condyle prosthesis and a preparation method thereof, and an artificial knee joint. Background Art

[0002] Cobalt-chromium-molybdenum alloy and titanium alloy are the two most commonly used metal materials for artificial joint prostheses. The elastic modulus of titanium alloy is relatively closer to that of bone tissue and lighter in weight, which can reduce adverse consequences such as bone resorption caused by stress shielding after prosthesis implantation. However, compared with cobalt-chromium-molybdenum alloy, the surface polishing of titanium alloy materials during processing is more difficult, and its wear resistance (especially the ability to resist scratch damage) is significantly lower than that of cobalt-chromium-molybdenum alloy, making titanium alloy unsuitable for use as a friction interface. At the same time, due to the poor fluidity of titanium alloy after melting, it has not been used for casting. Therefore, cobalt-chromium-molybdenum alloy is currently the manufacturing material used for the femoral condyle components of most knee prostheses, but its wear resistance to the friction pair polyethylene still needs to be greatly improved. At the same time, allergy to the nickel element in cobalt-chromium-molybdenum alloy is one of the reasons for the failure of total knee replacement surgery in some patients, so other metal parts of artificial knee prostheses (such as tibial trays, etc.) are made of titanium alloy. Materials for the manufacture of femoral condyle components of artificial knee prostheses that can replace cobalt-chromium-molybdenum alloys have appeared or are being developed abroad, such as surface-ceramicized zirconium-niobium alloy materials and zirconium oxide-toughened alumina ceramics (fourth-generation bioceramics), but their wear rate on polyethylene is still too high. Summary of the invention

[0003] The purpose of the present invention is to provide a super wear-resistant titanium alloy femoral condyle prosthesis and a preparation method thereof, and an artificial knee joint. The friction coefficient of the interface between the femoral condyle prosthesis and the tibial pad (polyethylene) provided by the present invention is small, and the femoral condyle prosthesis has good friction reduction and wear resistance.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The invention provides an ultra-wear-resistant titanium alloy femoral condyle prosthesis, comprising a titanium alloy femoral condyle matrix and a hard carbon-based film attached to the surface of the titanium alloy femoral condyle matrix; the hard carbon-based film comprises a titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer stacked in sequence; the titanium carbide bottom layer is in contact with the titanium alloy femoral condyle matrix; the titanium carbide-carbon transition layer is composed of carbon and titanium carbide; the carbon-titanium carbide multilayer is composed of alternately stacked carbon layers and titanium carbide layers.

[0006] Preferably, the thickness of the titanium carbide bottom layer is 100-200 nm, the thickness of the titanium carbide-carbon transition layer is 100-200 nm, and the thickness of the amorphous carbon top layer is 50-100 nm.

[0007] Preferably, taking the total thickness of adjacent carbon layers and titanium carbide layers as a modulation period, the modulation period of the carbon-titanium carbide multilayer is 5-10 nm; and the total thickness of the carbon-titanium carbide multilayer is 550-1500 nm.

[0008] Preferably, the material of the titanium alloy femoral condyle matrix is ​​Ti6Al4V, Ti6Al7Nb, Ti13Nb13Zr, Ti5Al3Mo4Zr, Ti5Al2.5Fe, Ti40Ta, Ti15Mo3Nb, Ti12Mo6Zr2Fe, Ti35Nb7Zr5Ta, Ti15Mo, Ti12Mo5Zr3Al, Ti8Fe8Ta or Ti8Fe8Ta4Zr.

[0009] The present invention provides a method for preparing the super-wear-resistant titanium alloy femoral condyle prosthesis described in the above scheme, comprising the following steps:

[0010] According to the composition of the super wear-resistant titanium alloy femoral condyle matrix, the corresponding titanium alloy powder and the binder are mixed and granulated to obtain granules;

[0011] The pellets are injection molded to obtain a titanium alloy blank;

[0012] Debinding and sintering the titanium alloy blank in sequence to obtain a titanium alloy femoral condyle matrix;

[0013] A titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer are sequentially deposited on the surface of the titanium alloy femoral condyle matrix by magnetron sputtering to obtain the super wear-resistant titanium alloy femoral condyle prosthesis.

[0014] Preferably, in terms of mass percentage, the binder includes 55-65% polyoxymethylene, 10-12% polyethylene glycol, 20-25% low-density polyethylene, 1-3% polypropylene, 2-4% paraffin and 1-3% stearic acid; the mass of the binder is 10-15% of the mass of the titanium alloy powder; the debinding temperature is 250-500°C, and the time is 5-10 hours.

[0015] Preferably, the injection molding conditions include: injection temperature of 100-180°C, injection pressure of (8-12)×10 5 MPa, and the holding time is 5 to 45 seconds.

[0016] Preferably, the sintering vacuum degree is 3×10 -3 Below Pa, the sintering temperature is 1230-1280℃ and the holding time is 2-3h.

[0017] Preferably, the deposition conditions of the titanium carbide bottom layer include: the titanium carbide target current is 2.5 to 4A, the argon gas flow rate is 40 to 45 sccm, the bias voltage is -100 to -150V, and the deposition time is 10 to 15min;

[0018] The deposition conditions of the titanium carbide-carbon transition layer include: the titanium carbide target current is 2 to 3A, the graphite target current gradually increases from 0.5A to 2.5A, the bias voltage is -100 to -200V, the argon gas flow rate is 20 to 30sccm, and the deposition time is 10 to 15min;

[0019] The deposition conditions of the carbon-titanium carbide multilayer include: titanium carbide target current of 2 to 3A, graphite target current of 1.5 to 2.5A, bias voltage of -100 to -200V, argon gas flow rate of 20 to 30sccm, and deposition time of 1.5 to 4.5h;

[0020] The deposition conditions of the amorphous carbon top layer include: graphite target current of 2.5-3.5A, argon gas flow of 40-45sccm, bias voltage of -100--150V, bias voltage adjustment frequency of 0.5-1V / min, and deposition time of 10-15min.

[0021] The present invention provides an artificial knee joint, comprising the super-wear-resistant titanium alloy femoral condyle prosthesis described in the above scheme or the super-wear-resistant titanium alloy femoral condyle prosthesis prepared by the preparation method described in the above scheme.

[0022] The invention provides an ultra-wear-resistant titanium alloy femoral condyle prosthesis, comprising a titanium alloy femoral condyle matrix and a hard carbon-based film attached to the surface of the titanium alloy femoral condyle matrix; the hard carbon-based film comprises a titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer stacked in sequence; the titanium carbide bottom layer is in contact with the titanium alloy femoral condyle matrix; the titanium carbide-carbon transition layer is composed of carbon and titanium carbide; the carbon-titanium carbide multilayer is composed of alternately stacked carbon layers and titanium carbide layers.

[0023] The titanium alloy femoral condyle prosthesis of the present invention has a layer of hard carbon-based film attached to its surface, wherein the hard alloy film comprises a titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer stacked in sequence, wherein the titanium carbide bottom layer and the titanium carbide-carbon transition layer can improve the bonding force between the hard carbon-based film and the titanium alloy femoral condyle matrix, the carbon-titanium carbide multilayer structure improves the strength of the hard carbon-based film, and can release internal stress and maintain the stability of the film, while the amorphous carbon top layer located at the outermost side can give the hard carbon-based film a lower friction coefficient. The above structural design enables the overall hard carbon-based film to have both high strength (wear resistance) and a small friction coefficient (friction reduction), and good bonding force with the titanium alloy femoral condyle matrix.

[0024] The results of the examples show that the friction coefficient between the femoral condyle prosthesis provided by the present invention, the hard carbon-based film on the outside of the titanium alloy femoral condyle and the highly cross-linked ultra-high molecular weight polyethylene material can be as low as 0.02-0.04, which greatly reduces the wear of the polymer polyethylene gasket.

[0025] In addition, the present invention also has the following advantages:

[0026] Titanium alloy has good biocompatibility, reducing adverse reactions in the human body;

[0027] The elastic modulus of titanium alloy is relatively closer to that of bone tissue and lighter in weight, which can reduce adverse consequences such as bone resorption caused by stress shielding after prosthesis implantation;

[0028] The titanium alloy femoral condyle prosthesis and other titanium alloy parts of the existing artificial knee joint are made of the same metal (meaning they are all titanium alloys), which can reduce the corrosion caused by the difference in potential of different metals after the prosthesis is implanted;

[0029] The hard carbon-based film on the surface of the femoral condyle prosthesis has a stable structure and good biocompatibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The schematic diagram of the structure of the artificial knee joint of the present invention, wherein: 1-titanium alloy femoral condyle substrate, 2-hard carbon-based film, 3-gasket, 4-tibial tray;

[0031] Figure 2 It is a schematic diagram of the structure of the carbon-based hard film on the outer surface of the femoral condyle of the present invention;

[0032] Figure 3 The SEM images of the hard carbon-based film on the outer surface of the femoral condyle in Example 1 of the present invention are as follows: (a) the surface morphology of the hard carbon-based film; (b) the cross-sectional morphology of the hard carbon-based film;

[0033] Figure 4 This is a TEM image of the multilayer structure in the hard carbon-based film on the outer surface of the femoral condyle in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The invention provides an ultra-wear-resistant titanium alloy femoral condyle prosthesis, comprising a titanium alloy femoral condyle matrix and a hard carbon-based film attached to the surface of the titanium alloy femoral condyle matrix; the hard carbon-based film comprises a titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer stacked in sequence; the titanium carbide bottom layer is in contact with the titanium alloy femoral condyle matrix; the titanium carbide-carbon transition layer is composed of carbon and titanium carbide; the carbon-titanium carbide multilayer is composed of alternately stacked carbon layers and titanium carbide layers.

[0035] The ultra-wear-resistant titanium alloy femoral condyle prosthesis provided by the present invention comprises a titanium alloy femoral condyle matrix, and the material of the titanium alloy femoral condyle matrix is ​​preferably Ti6Al4V, Ti6Al7Nb, Ti13Nb13Zr, Ti5Al3Mo4Zr, Ti5Al2.5Fe, Ti40Ta, Ti15Mo3Nb, Ti12Mo6Zr2Fe, Ti35Nb7Zr5Ta, Ti15Mo, Ti12Mo5Zr3Al, Ti8Fe8Ta or Ti8Fe8Ta4Zr. The femoral condyle prosthesis of the present invention adopts a titanium alloy matrix, has good biocompatibility, and reduces adverse reactions in the human body; in addition, the elastic modulus of the titanium alloy is relatively closer to that of bone tissue, and is lighter in weight, which can reduce adverse results such as bone absorption caused by stress shielding after implantation of the prosthesis.

[0036] The ultra-wear-resistant titanium alloy femoral condyle prosthesis provided by the present invention comprises a hard carbon-based film attached to the surface of the titanium alloy femoral condyle substrate. In the present invention, the hardness of the hard carbon-based film is preferably 15 to 22 GPa, more preferably 17 to 20 GPa.

[0037] In the present invention, the hard carbon-based film comprises a titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer stacked in sequence. Figure 2 shown.

[0038] In the present invention, the thickness of the titanium carbide bottom layer is preferably 100 to 200 nm, more preferably 120 to 180 nm, and further preferably 140 to 160 nm.

[0039] In the present invention, the thickness of the titanium carbide-carbon transition layer is preferably 100 to 200 nm, more preferably 120 to 180 nm, and further preferably 140 to 160 nm. In the present invention, the titanium carbide-carbon transition layer is composed of carbon and titanium carbide, that is, the titanium carbide-carbon transition layer is a mixed structure obtained by simultaneously depositing titanium carbide and carbon. The present invention contacts the titanium carbide bottom layer with the titanium alloy femoral condyle substrate, and then plates the titanium carbide-carbon transition layer, which can achieve a gradual transition from the substrate to the carbon layer, which is beneficial to improving the bonding strength between the hard carbon-based film and the titanium alloy femoral condyle substrate.

[0040] In the present invention, the carbon-titanium carbide multilayer is composed of alternately stacked carbon layers and titanium carbide layers, and the thickness of each carbon layer is independently preferably 2 to 5 nm, more preferably 3 to 4 nm; the thickness of each titanium carbide layer is independently preferably 3 to 5 nm, more preferably 3.5 to 4.5 nm; the total thickness of the carbon-titanium carbide multilayer is preferably 550 to 1500 nm, more preferably 700 to 1200 nm, and further preferably 800 to 1000 nm. Taking the total thickness of adjacent carbon layers and titanium carbide layers as a modulation period, the modulation period of the carbon-titanium carbide multilayer (i.e., the thickness of one carbon layer + one titanium carbide layer) is preferably 5 to 10 nm. In the present invention, the carbon layer in the carbon-titanium carbide multilayer or the titanium carbide layer in the carbon-titanium carbide multilayer in contact with the titanium carbide-carbon transition layer may be, and the present invention does not make special restrictions. In the present invention, the carbon-titanium carbide multilayer structure improves the strength of the hard carbon-based film, and can release internal stress and maintain the stability of the film.

[0041] In the present invention, the thickness of the amorphous carbon top layer is preferably 50 to 100 nm, more preferably 60 to 90 nm, and further preferably 70 to 80 nm. In the present invention, the outermost amorphous carbon top layer can give the hard carbon-based film a lower friction coefficient. In the present invention, the amorphous carbon top layer is preferably deposited by a bias gradient method, which can realize the gradual transition of the film layer from a soft layer to a hard layer, thereby improving its tribological properties.

[0042] The above structural design enables the overall hard carbon-based film to have both high strength (wear resistance) and low friction coefficient (friction reduction), and has good bonding strength with the titanium alloy femoral condyle matrix.

[0043] The present invention provides a method for preparing the super-wear-resistant titanium alloy femoral condyle prosthesis described in the above scheme, comprising the following steps:

[0044] According to the composition of the super wear-resistant titanium alloy femoral condyle matrix, the corresponding titanium alloy powder and the binder are mixed and granulated to obtain granules;

[0045] The pellets are injection molded to obtain a titanium alloy blank;

[0046] Debinding and sintering the titanium alloy blank in sequence to obtain a titanium alloy femoral condyle matrix;

[0047] A titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer are sequentially deposited on the surface of the titanium alloy femoral condyle matrix by magnetron sputtering to obtain the super wear-resistant titanium alloy femoral condyle prosthesis.

[0048] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.

[0049] According to the composition of the super wear-resistant titanium alloy femoral condyle matrix, the present invention mixes corresponding titanium alloy powder and a binder to form granules to obtain granules.

[0050] In the present invention, the particle size of the titanium alloy powder is preferably 15-50 μm; in terms of mass percentage, the binder preferably includes 55-65% polyoxymethylene, 10-12% polyethylene glycol, 20-25% low-density polyethylene, 1-3% polypropylene, 2-4% paraffin and 1-3% stearic acid; further, preferably includes 58-63% polyoxymethylene, 10.5-11.5% polyethylene glycol, 22-23% low-density polyethylene, 1.5-2.5% polypropylene, 2.5-3.5% paraffin, and 1.5-2.5% stearic acid. In the present invention, the mass of the binder is preferably 10-15% of the mass of the titanium alloy powder, more preferably 11-14%, and further preferably 12-13%.

[0051] In the present invention, the granulation is preferably carried out in a banburying granulator; the present invention preferably adds the titanium alloy powder and the binder into a banburying granulator for banburying, and then granulates. In the present invention, the banburying temperature is preferably 100 to 200°C, more preferably 120 to 180°C, and further preferably 140 to 160°C; the banburying time is preferably 0.5 to 2 hours, more preferably 1 to 1.5 hours. In the present invention, the banburying is preferably carried out under stirring conditions, and the stirring rate is preferably 800 to 1200 rpm.

[0052] After obtaining the pellets, the present invention performs injection molding on the pellets to obtain a titanium alloy blank.

[0053] Before the injection molding, the present invention preferably designs the injection molding mold and pouring system according to the structural characteristics of the femoral condyle prosthesis and the shrinkage rate of the material.

[0054] In the present invention, the injection molding conditions preferably include: injection temperature of 100 to 180°C, injection pressure of (8 to 12)×10 5 MPa, the holding time is 5 to 45 seconds; as a further preferred solution, the injection temperature is more preferably 120 to 160°C, and more preferably 140 to 150°C; the injection pressure is more preferably (9 to 10)×10 5 MPa; the holding time is more preferably 10 to 40 seconds, and further preferably 20 to 30 seconds.

[0055] After obtaining the titanium alloy blank, the present invention sequentially performs debinding and sintering on the titanium alloy blank to obtain a titanium alloy femoral condyle matrix.

[0056] In the present invention, the debinding temperature is preferably 250-500°C, more preferably 300-450°C, and further preferably 350-400°C; the debinding time is preferably 5-10h, more preferably 6-9h, and further preferably 7-8h. In the present invention, the titanium alloy blank is preferably placed in a debinding furnace containing an oxalic acid medium for debinding.

[0057] In the present invention, the vacuum degree of sintering is preferably 3×10 -3 Pa or less; the sintering temperature is preferably 1230-1280°C, more preferably 1240-1270°C, further preferably 1250-1260°C; the sintering holding time is preferably 2-3h.

[0058] After obtaining the titanium alloy femoral condyle matrix, the present invention uses magnetron sputtering to sequentially deposit a titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer on the surface of the titanium alloy femoral condyle matrix to obtain the ultra-wear-resistant titanium alloy femoral condyle prosthesis.

[0059] In the present invention, the magnetron sputtering is preferably closed-field unbalanced magnetron sputtering.

[0060] The present invention preferably places the titanium alloy femoral condyle matrix on a rotating worktable, and places a graphite target, a titanium carbide target, a graphite target and a titanium carbide target at 90° on the periphery of the rotating worktable (that is, the angle between any adjacent targets of the four targets is 90°), pre-evacuates the cavity, introduces argon gas, performs pre-sputtering, and then starts to deposit the titanium carbide bottom layer.

[0061] In the present invention, the pre-sputtering time is preferably 30 minutes, and the bias voltage is preferably -500 V. The present invention removes oxide impurities on the surface of the titanium alloy femoral condyle matrix by pre-sputtering.

[0062] The present invention deposits a titanium carbide bottom layer on the surface of a titanium alloy femoral condyle matrix.

[0063] In the present invention, the deposition conditions of the titanium carbide bottom layer preferably include: the titanium carbide target current is 2.5 to 4A, more preferably 2.5 to 3.5A; the argon gas flow rate is 40 to 45 sccm, more preferably 42 to 44 sccm; the bias voltage is preferably -100 to -150V, more preferably -110 to -140V, and further preferably -120 to -130V; the deposition time is 10 to 15min. In the present invention, when depositing the titanium carbide bottom layer, the workbench does not rotate, and the two titanium carbide targets work simultaneously.

[0064] After forming the titanium carbide bottom layer, the present invention deposits a titanium carbide-carbon transition layer on the surface of the titanium carbide bottom layer. In the present invention, the deposition conditions of the titanium carbide-carbon transition layer preferably include: the titanium carbide target current is 2 to 3A, more preferably 2.2 to 2.8A, and further preferably 2.4 to 2.6A; the graphite target current gradually increases from 0.5A to 2.5A; the bias voltage is -100 to -200V, more preferably -120 to -180V, and further preferably -140 to -160V; the argon gas flow rate is preferably 20 to 30sccm, more preferably 22 to 28sccm, and further preferably 24 to 26sccm; the deposition time is preferably 10 to 15min, and further preferably 12 to 13min. In the present invention, when depositing the titanium carbide-carbon transition layer, the workbench does not rotate, and the four targets work simultaneously.

[0065] After the titanium carbide-carbon transition layer is formed, the present invention deposits carbon-titanium carbide multiple layers on the surface of the titanium carbide-carbon transition layer.

[0066] In the present invention, the deposition conditions of the carbon-titanium carbide multilayer preferably include: the titanium carbide target current is 2 to 3A, more preferably 2.2 to 2.8A, and further preferably 2.4 to 2.6A; the graphite target current is 1.5 to 2.5A, more preferably 1.8 to 2.3A, and further preferably 2 to 2.1A; the bias voltage is -100 to -200V, preferably -120 to -180V, and further preferably -140 to -160V; the argon gas flow rate is 20 to 30sccm, more preferably 22 to 28sccm, and further preferably 24 to 26sccm; the deposition time is 1.5 to 4.5h, more preferably 2 to 4h, and further preferably 2.5 to 3.5h. In the present invention, during the deposition of the carbon-titanium carbide multilayer, the rotation speed of the rotary table is preferably 3 to 5rpm, and four targets work simultaneously.

[0067] After forming the carbon-titanium carbide multilayer, the present invention deposits an amorphous carbon top layer on the surface of the carbon-titanium carbide multilayer. In the present invention, the deposition conditions of the amorphous carbon top layer preferably include: the graphite target current is 2.5 to 3.5A, more preferably 2.7 to 3.3A, and further preferably 2.9 to 3.1A; the argon gas flow rate is 40 to 45sccm, and further preferably 42 to 43sccm; the bias voltage is -100 to -150V, more preferably -110 to -140V, and further preferably -120 to -130V; the bias voltage adjustment frequency is 0.5 to 1V / min, more preferably 0.6 to 0.9V / min, and further preferably 0.7 to 0.8V / min; the deposition time is preferably 10 to 15min, more preferably 11 to 14min, and further preferably 12 to 13min. In the present invention, when depositing the amorphous carbon top layer, the workbench does not rotate, and the two graphite targets work simultaneously.

[0068] The present invention provides an artificial knee joint, comprising the ultra-wear-resistant titanium alloy femoral condyle prosthesis described in the above scheme or the ultra-wear-resistant titanium alloy femoral condyle prosthesis prepared by the preparation method described in the above scheme; preferably also comprising a titanium alloy tibial tray and a gasket; the material of the gasket is preferably polyethylene, more preferably highly cross-linked ultra-high molecular weight polyethylene.

[0069] Figure 1 FIG. 1 is a schematic diagram of the structure of the artificial knee joint of the present invention. Figure 1 As shown, 1 is a titanium alloy femoral condyle matrix, 2 is a hard carbon-based film, 3 is a gasket, and 4 is a tibial tray.

[0070] In the femoral condyle prosthesis provided by the present invention, the friction coefficient between the hard carbon-based film on the outside of the titanium alloy femoral condyle and the highly cross-linked ultra-high molecular weight polyethylene material can be as low as 0.02-0.04, which greatly reduces the wear of the high molecular polyethylene gasket.

[0071] The ultra-wear-resistant titanium alloy femoral condyle prosthesis and its preparation method and artificial knee joint provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0072] Example 1

[0073] 1) preparing a binder according to the following mass ratio: 65% of polyoxymethylene (POM), 10% of polyethylene glycol (PEG), 20% of low-density polyethylene (LDPE), 1% of polypropylene (PP), 3% of paraffin wax (PW), and 1% of stearic acid (SA); then putting the binder (15% of the mass of the titanium alloy powder) and Ti6Al4V powder with a particle size of 15 to 50 μm into a banbury granulator to prepare pellets;

[0074] 2) Injection molding: put the prepared pellets into the injection machine trough, then heat and inject. Injection process: injection temperature is 150℃, injection pressure is 8×10 5 MPa, holding time is 30 seconds;

[0075] 3) Debinding: The injection molded titanium alloy blank is placed in a debinding furnace containing oxalic acid medium for debinding at a temperature of 400°C for 6 hours;

[0076] 4) Sintering: After debinding, vacuum sintering is carried out. Sintering process: vacuum degree is 3×10 -3 Pa, sintering temperature is 1250℃, keep warm for 3h, prepare titanium alloy femoral condyle matrix;

[0077] 5) Place the titanium alloy femoral condyle matrix on a rotating worktable, and place a graphite target, a titanium carbide target, a graphite target, and a titanium carbide target at 90° on the periphery of the rotating worktable, pre-evacuate the cavity, introduce argon gas, and bombard for 30 minutes at a bias voltage of -500 V;

[0078] 6) Using a 2.5A titanium carbide target current, the argon flow rate was maintained at 42sccm, and the bias voltage was -110V to deposit a titanium carbide bottom layer for 10min with a thickness of 100nm;

[0079] 7) Using a 3A titanium carbide target current, the graphite target current was gradually increased from 0.5A to 2.5A, and a bias voltage of -200V was used to deposit a titanium carbide-carbon transition layer on the titanium carbide bottom layer. The argon gas flow rate was controlled at 25sccm, the deposition time was 15min, and the thickness was 200nm;

[0080] 8) using a titanium carbide target current of 3A, a graphite target current of 2A, and a bias voltage of -150V to deposit an amorphous carbon-titanium carbide multilayer structure, wherein the rotating table speed is 5rpm, the argon gas flow rate is controlled at 25sccm, the deposition time is 3h, and the total thickness is 800nm, wherein the modulation period of the amorphous carbon-titanium carbide multilayer structure is 5nm;

[0081] 9) The titanium carbide target current was 0, a graphite target current of 3.5 A, an argon gas flow rate of 45 sccm, a bias voltage of -110 to -125 V, a bias voltage adjustment frequency of 1 V / min, a deposition time of 15 min, and an amorphous carbon top layer with a thickness of 100 nm was formed to obtain a titanium alloy femoral condyle prosthesis.

[0082] Performance Testing:

[0083] Example 1 The titanium alloy femoral condyle prosthesis does not deform under a pressure of 1500kg, the yield strength is 860MPa, the hardness of the surface hard carbon-based film is 19GPa, and the high cross-linked polyethylene material (Mitsubishi Chemical, Chirulen R The friction coefficient of 1020X highly cross-linked ultra-high molecular weight polyethylene is 0.03.

[0084] The specific test method is: the friction and wear performance of the hard carbon-based film is analyzed and tested by a pin-on-disc friction test. The titanium alloy disk substrate is prepared by the injection molding process and formula described in steps 1) to 4) of Example 1, and the hard carbon-based film is plated on the titanium alloy disk substrate by steps 5) to 9), and the pins required for the friction and wear test are machined by highly cross-linked polyethylene (the same material as the artificial knee joint gasket of the present invention). In the test, the pin and the titanium alloy disk coated with the hard carbon-based film form a friction pair. The friction experiment was carried out at room temperature in an environment of simulated body fluid (protein content of 30±2mg / mL, 17g / L calf serum as a lubricating medium). The load was 5N, the relative sliding speed was 0.25m / s, the test duration was 60min, and the average friction coefficient was obtained.

[0085] Figure 3 The SEM images of the hard carbon-based film on the outer surface of the femoral condyle in Example 1 of the present invention are as follows: (a) surface morphology of the hard carbon-based film; (b) cross-sectional morphology of the hard carbon-based film; as can be seen from (a), the surface layer of the hard carbon film is very flat and has a high surface finish; as can be seen from (b), the overall structure of the carbon film is continuous, without obvious defects such as interlayer cracks.

[0086] Figure 4 This is a TEM image of the multilayer structure in the hard carbon-based film on the outer surface of the femoral condyle in Example 1 of the present invention. The multilayer structure can be clearly seen; the small image in the upper right corner is an electron diffraction image of the material, indicating that the multilayer structure presents an amorphous structure.

[0087] Example 2

[0088] 1) preparing a binder according to the following mass proportions: 62% of polyoxymethylene (POM), 12% of polyethylene glycol (PEG), 21% of low-density polyethylene (LDPE), 1% of polypropylene (PP), 3% of paraffin wax (PW), and 1% of stearic acid (SA); then putting the binder (accounting for 12% of the mass of the titanium alloy powder) and Ti6Al7Nb powder with a particle size of 15 to 50 μm into a banbury granulator to prepare pellets;

[0089] 2) Injection molding: Put the prepared pellets into the injection machine trough, then heat and inject. Injection process: The injection temperature is 180℃ and the injection pressure is 8×10 5 MPa, holding time is 30 seconds;

[0090] 3) Debinding: The injection molded titanium alloy blank is placed in a debinding furnace containing oxalic acid medium for debinding at a temperature of 450°C for 5 hours;

[0091] 4) Sintering: After debinding, vacuum sintering is carried out. Sintering process: Vacuum degree: 3×10 -3 Pa, sintering temperature is 1280℃, heat preservation is 3h, and titanium alloy femoral condyle matrix is ​​obtained;

[0092] 5) Place the titanium alloy femoral condyle matrix on a rotating worktable, and place a graphite target, a titanium carbide target, a graphite target, and a titanium carbide target at 90° on the periphery of the rotating worktable, pre-evacuate the cavity, introduce argon gas, and bombard for 30 minutes at a bias voltage of -500 V;

[0093] 6) Using a 3.5A titanium carbide target current, the argon flow rate was maintained at 44sccm, and the bias voltage was -140V to deposit a titanium carbide bottom layer for 15min with a thickness of 200nm;

[0094] 7) Using a 3A titanium carbide target current, the graphite target current was gradually increased from 0.5A to 2.5A, and a bias voltage of -200V was used to deposit a titanium carbide-carbon transition layer on the titanium carbide bottom layer. The argon gas flow rate was controlled at 25sccm, the deposition time was 15min, and the thickness was 200nm;

[0095] 8) using a titanium carbide target current of 3A, a graphite target current of 2.5A, and a bias voltage of -150V to deposit an amorphous carbon-titanium carbide multilayer structure, wherein the rotating table speed is 3rpm, the argon gas flow rate is controlled at 25sccm, the deposition time is 4h, and the total thickness is 1000nm, wherein the modulation period of the amorphous carbon-titanium carbide multilayer structure is 10nm;

[0096] 9) The titanium carbide target current was 0, a graphite target current of 3.5 A, an argon gas flow rate of 45 sccm, a bias voltage of -110 to -125 V, a bias voltage adjustment frequency of 1 V / min, a deposition time of 15 min, and an amorphous carbon top layer with a thickness of 100 nm was formed to obtain a titanium alloy femoral condyle prosthesis.

[0097] The titanium alloy femoral condyle prosthesis of Example 2 does not deform under a pressure of 1500 kg, has a yield strength of 780 MPa, a hardness of the surface carbon-based film of 22 GPa, and a friction coefficient of 0.03 to a highly cross-linked polyethylene material.

[0098] Example 3

[0099] 1) preparing a binder according to the following proportions: 65% of polyoxymethylene (POM), 10% of polyethylene glycol (PEG), 20% of low-density polyethylene (LDPE), 2% of polypropylene (PP), 3% of paraffin wax (PW), and 1% of stearic acid (SA); then putting the binder (accounting for 11% of the mass of the titanium alloy powder) and Ti35Nb7Zr5Ta powder with a particle size of 15 to 50 μm into a banbury granulator to prepare pellets;

[0100] 2) Injection molding: Put the prepared pellets into the injection machine trough, then heat and inject. Injection process: injection temperature is 160℃, injection pressure is 8×10 5 MPa, holding time is 40 seconds;

[0101] 3) Debinding: The injection molded titanium alloy blank is placed in a debinding furnace containing oxalic acid medium for debinding at a temperature of 350°C for 6 hours;

[0102] 4) Sintering: After debinding, vacuum sintering is carried out. Sintering process: Vacuum degree: 3×10 -3 Pa, sintering temperature is 1230℃, keep warm for 4h, prepare titanium alloy femoral condyle matrix;

[0103] 5) Place the titanium alloy femoral condyle matrix on a rotating worktable, and place a graphite target, a titanium carbide target, a graphite target, and a titanium carbide target at 90° on the periphery of the rotating worktable, pre-evacuate the cavity, introduce argon gas, and bombard for 30 minutes at a bias voltage of -500 V;

[0104] 6) Using a 3.0A titanium carbide target current, the argon flow rate was maintained at 40sccm, and the bias voltage was -140V to deposit a titanium carbide bottom layer for 12 minutes with a thickness of 150nm;

[0105] 7) Using a 2.8A titanium carbide target current, the graphite target current was gradually increased from 0.5A to 2.5A, and a bias voltage of -150V was used to deposit a titanium carbide-carbon transition layer on the titanium carbide bottom layer. The argon gas flow rate was controlled at 30sccm, the deposition time was 12min, and the thickness was 150nm;

[0106] 8) using a titanium carbide target current of 3.0A, a graphite target current of 2.5A, and a bias voltage of -150V to deposit an amorphous carbon-titanium carbide multilayer structure, wherein the rotating table speed is 4rpm, the argon gas flow rate is controlled at 25sccm, the deposition time is 4h, and the total thickness is 1200nm, wherein the modulation period of the amorphous carbon-titanium carbide multilayer structure is 8nm;

[0107] 9) The titanium carbide target current was 0, the graphite target current was 2.5A, the argon flow rate was 45sccm, the bias voltage was -120 to -125V, the bias voltage adjustment frequency was 0.5V / min, the deposition time was 10min, and an amorphous carbon top layer with a thickness of 50nm was formed to obtain a titanium alloy femoral condyle prosthesis.

[0108] The titanium alloy femoral condyle prosthesis of Example 3 does not deform under a pressure of 1500 kg, has a yield strength of 835 MPa, a hardness of the surface carbon-based film of 20 GPa, and a friction coefficient of 0.04 to a highly cross-linked polyethylene material.

[0109] Comparative Example 1

[0110] A titanium alloy femoral condyle substrate was prepared according to the method of Example 1.

[0111] The friction coefficient of the titanium alloy femoral condyle substrate without carbon film coating in the simulated body fluid of comparative example 1 (the same test method as in example 1) is 0.15 to 0.2. It can be seen that the present invention reduces the friction coefficient of the titanium alloy femoral condyle prosthesis and improves its wear resistance by coating the hard carbon-based film on the surface of the titanium alloy femoral condyle substrate.

[0112] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A super wear-resistant titanium alloy femoral condyle prosthesis, characterized in that: The invention comprises a titanium alloy femoral condyle matrix and a hard carbon-based film attached to the surface of the titanium alloy femoral condyle matrix; the hard carbon-based film comprises a titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer stacked in sequence; the titanium carbide bottom layer is in contact with the titanium alloy femoral condyle matrix; the titanium carbide-carbon transition layer is composed of carbon and titanium carbide; the carbon-titanium carbide multilayer is composed of alternately stacked carbon layers and titanium carbide layers; The thickness of the titanium carbide bottom layer is 100-200 nm, the thickness of the titanium carbide-carbon transition layer is 100-200 nm, and the thickness of the amorphous carbon top layer is 50-100 nm; Taking the total thickness of adjacent carbon layers and titanium carbide layers as a modulation period, the modulation period of the carbon-titanium carbide multilayer is 5-10 nm; the total thickness of the carbon-titanium carbide multilayer is 550-1500 nm.

2. The ultra-wear-resistant titanium alloy femoral condyle prosthesis according to claim 1, characterized in that: The material of the titanium alloy femoral condyle matrix is ​​Ti6Al4V, Ti6Al7Nb, Ti13Nb13Zr, Ti5Al3Mo4Zr, Ti5Al2.5Fe, Ti40Ta, Ti15Mo3Nb, Ti12Mo6Zr2Fe, Ti35Nb7Zr5Ta, Ti15Mo, Ti12Mo5Zr3Al, Ti8Fe8Ta or Ti8Fe8Ta4Zr.

3. The method for preparing the super-wear-resistant titanium alloy femoral condyle prosthesis according to any one of claims 1 to 2, characterized in that: The following steps are involved: According to the composition of the super wear-resistant titanium alloy femoral condyle matrix, the corresponding titanium alloy powder is mixed with a binder to form granules to obtain granules; The pellets are injection molded to obtain a titanium alloy blank; Debinding and sintering the titanium alloy blank in sequence to obtain a titanium alloy femoral condyle matrix; A titanium carbide bottom layer, a titanium carbide-carbon transition layer, a carbon-titanium carbide multilayer and an amorphous carbon top layer are sequentially deposited on the surface of the titanium alloy femoral condyle matrix by magnetron sputtering to obtain the super wear-resistant titanium alloy femoral condyle prosthesis.

4. The preparation method according to claim 3, characterized in that: Calculated in percentage by mass, the binder includes 55-65% polyoxymethylene, 10-12% polyethylene glycol, 20-25% low-density polyethylene, 1-3% polypropylene, 2-4% paraffin and 1-3% stearic acid; the mass of the binder is 10-15% of the mass of the titanium alloy powder; the debinding temperature is 250-500°C and the time is 5-10h.

5. The preparation method according to claim 3, characterized in that: The injection molding conditions include: injection temperature of 100-180°C, injection pressure of (8-12)×10 5 MPa, and the holding time is 5 to 45 seconds.

6. The preparation method according to claim 3, characterized in that: The vacuum degree of the sintering is 3×10 -3 Below Pa, the sintering temperature is 1230-1280℃ and the holding time is 2-3h.

7. The preparation method according to claim 3, characterized in that: The deposition conditions of the titanium carbide bottom layer include: the titanium carbide target current is 2.5 to 4A, the argon gas flow rate is 40 to 45 sccm, the bias voltage is -100 to -150V, and the deposition time is 10 to 15 minutes; The deposition conditions of the titanium carbide-carbon transition layer include: the titanium carbide target current is 2 to 3A, the graphite target current gradually increases from 0.5A to 2.5A, the bias voltage is -100 to -200V, the argon gas flow rate is 20 to 30sccm, and the deposition time is 10 to 15min; The deposition conditions of the carbon-titanium carbide multilayer include: titanium carbide target current of 2 to 3A, graphite target current of 1.5 to 2.5A, bias voltage of -100 to -200V, argon gas flow rate of 20 to 30sccm, and deposition time of 1.5 to 4.5h; The deposition conditions of the amorphous carbon top layer include: graphite target current of 2.5-3.5A, argon gas flow of 40-45sccm, bias voltage of -100--150V, bias voltage adjustment frequency of 0.5-1V / min, and deposition time of 10-15min.

8. An artificial knee joint, characterized in that: The invention comprises the super-wear-resistant titanium alloy femoral condyle prosthesis according to any one of claims 1 to 2 or the super-wear-resistant titanium alloy femoral condyle prosthesis prepared by the preparation method according to any one of claims 3 to 7.